0
$\begingroup$

Prove that:

$\tan^{-1}{6x-8x^3\over 1-12x^2} + \tan^{-1}{4x\over 1-4x^2} = \tan^{-1}2x$, $|2x|<{1\over \sqrt3}$

$\endgroup$
  • $\begingroup$ Hint: take the tangent of both members. $\endgroup$ – Yves Daoust May 5 '16 at 10:49
1
$\begingroup$

Hint:

If $|\alpha\beta|<1$, then $$\arctan \alpha + \arctan \beta =\arctan\frac{\alpha+\beta}{1-\alpha\beta}$$

$\endgroup$
0
$\begingroup$

HINT:

Use the definition of Principal values,

As $-\dfrac\pi6\le\tan^{-1}(2x)\le\dfrac\pi6,$ $\tan^{-1}\dfrac{6x-8x^3}{1-12x^2}=\tan^{-1}\dfrac{3(2x)-(2x)^3}{1-3(2x)^2} =3\tan^{-1}(2x)$

As $-\dfrac\pi4\le\tan^{-1}(2x)\le\dfrac\pi4,$ $ \tan^{-1}\dfrac{4x}{1-4x^2}= \tan^{-1}\dfrac{2(2x)}{1-(2x)^2}=2\tan^{-1}(2x)$

$\endgroup$
0
$\begingroup$

With some labor, you can prove more. Consider $$ f(x)=\arctan\frac{6x-8x^3}{1-12x^2} \color{red}{-} \arctan\frac{4x}{1-4x^2} $$ which is defined for $x\notin\{1/2,-1/2,1/\sqrt{12},-1/\sqrt{12}\}$. Note the minus sign, otherwise the identity is false.

We can compute the derivative; first, the derivatives of the two fractions are, respectively, $$ \frac{6(1+4x^2)^2}{(1-12x^2)^2}, \qquad \frac{4(1+4x^2)}{(1-4x^2)^2} $$ Moreover $$ 1+\left(\frac{6x-8x^3}{1-12x^2}\right)^2= \frac{1+12x^2+48x^4+64x^6}{(1-12x^2)^2}=\frac{(1+4x^2)^3}{(1-12x^2)^2} $$ and $$ 1+\left(\frac{4x}{1-4x^2}\right)^2=\frac{1+8x^2+16x^4}{(1-4x^2)^2}= \frac{(1+4x^2)^2}{(1-4x^2)^2} $$ so we have $$ f'(x)=\frac{6}{1+4x^2}-\frac{4}{1+4x^2}=\frac{2}{1+4x^2} $$ which is the same as the derivative of $g(x)=\arctan(2x)$. Thus we can say that $$ f(x)=\begin{cases} c_1+\arctan(2x) & x<-1/2 \\[4px] c_2+\arctan(2x) & -1/2<x<-1/\sqrt{12} \\[4px] c_3+\arctan(2x) & -1/\sqrt{12}<x<1/\sqrt{12} \\[4px] c_4+\arctan(2x) & 1/\sqrt{12}<x<1/2 \\[4px] c_5+\arctan(2x) & x>1/2 \end{cases} $$ Since you're interested in $c_3$, just note that $f(0)=0$, so $c_3=0$.

For completeness, we can compute $$ c_1=\pi, \quad c_2=\pi/2, \quad c_3=0, \quad c_4=\pi \quad c_5=0 $$


Here's a way to see that your formula is wrong:

bc 1.06
Copyright 1991-1994, 1997, 1998, 2000 Free Software Foundation, Inc.
This is free software with ABSOLUTELY NO WARRANTY.
For details type `warranty'. 
x=1/(2*sqrt(12))
a((6*x-8*x^3)/(1-12*x^2))+a(4*x/(1-4*x^2))
1.40517450751406798853
a(2*x)
.28103490150281359770
a((6*x-8*x^3)/(1-12*x^2))-a(4*x/(1-4*x^2))
.28103490150281359773
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.